2012
DOI: 10.1179/1574077312z.0000000005
|View full text |Cite
|
Sign up to set email alerts
|

Holocaust Archaeology: Archaeological Approaches to Landscapes of Nazi Genocide and Persecution

Abstract: The landscapes and material remains of the Holocaust survive in various forms as physical reminders of the suffering and persecution of this period in European history. However, whilst clearly defined historical narratives exist, many of the archaeological remnants of these sites remain ill-defined, unrecorded and even, in some cases, unlocated. Such a situation has arisen as a result of a number of political, social, ethical and religious factors which, coupled with the scale of the crimes, has often inhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(14 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…A comparative scale seemed to impose itself in the first instance because of the juxtaposition of excavations at the Columbia concentration camp and the forced labor camps—although they are clearly very different orders of repression. We also found that our ability to analyze and interpret our findings was curtailed by the near absence of reports on excavations at other Nazi forced labor camps; such work began only in the late 1990s (Sturdy Colls ; Theune :58), and publications are mostly confined to very brief reports in regional journals (see bibliography in Theune ). We wanted to know whether similar items of daily life were found in other camps, whether there were marked differences in quantities, and whether the details of the construction of the barracks were the same or not.…”
Section: * * * * *mentioning
confidence: 98%
See 1 more Smart Citation
“…A comparative scale seemed to impose itself in the first instance because of the juxtaposition of excavations at the Columbia concentration camp and the forced labor camps—although they are clearly very different orders of repression. We also found that our ability to analyze and interpret our findings was curtailed by the near absence of reports on excavations at other Nazi forced labor camps; such work began only in the late 1990s (Sturdy Colls ; Theune :58), and publications are mostly confined to very brief reports in regional journals (see bibliography in Theune ). We wanted to know whether similar items of daily life were found in other camps, whether there were marked differences in quantities, and whether the details of the construction of the barracks were the same or not.…”
Section: * * * * *mentioning
confidence: 98%
“…They are—but almost entirely within the framework of mandated salvage projects, the reports of which land in the gray literature in state historical preservation offices, the objects in the cold storage of huge repositories. There are some exceptions (Hirte ; Sturdy Colls ; Theune , ); intriguingly, it is nonarchaeologists who have often been the initiators of archaeological work (Rürup ). But there is nowhere in Germany where students can specialize in the study of archaeology of the contemporary past, something that is particularly fatal in an academic landscape in which disciplinary boundaries, at least in the humanities and social sciences, are often still revered as quasi‐sacred…”
Section: * * * * *mentioning
confidence: 99%
“…Since the work began, considerable interest has come from the Geophysical side of the Geography department at Staffordshire University, particularly in the use of automating the collection of data in WWII concentration camp grave sites [18][19][20] and Fig. 9.…”
Section: Conclusion and Further Workmentioning
confidence: 99%
“…The archaeological research of both conflicts has recently been extensively developing in Europe. PoW camps, concentration camps, and death camps have been analyzed using different kinds of archaeological methods (Myers and Moshenska 2011; Carr 2012, 2013;Starzmann 2015;Sturdy Colls 2012. The same may be said about bunkers, trenches, mass graves, battlefields, no man's lands, and other sites that were the theaters of the World Wars (Theune 2013;Olsen and Witmore 2014;Passmore et al 2014;Capps Tunwell et al 2015;Kajda and Frąckowiak 2015).…”
mentioning
confidence: 96%